ANALISIS IMPLEMENTASI DASHBOARD MONITORING PRODUKTIVITAS DEVELOPER MENGGUNAKAN INTEGRASI GITLAB API DAN N8N BERBASIS WEB DENGAN METODE PROTOTYPE - Ulung Wira Yuda; Wydyanto (Jurnal Publikasi Manajemen Informatika, 2026)
The rapid development of information technology has encouraged organizations to implement monitoring systems capable of providing fast, accurate, and integrated information. In software development processes, developer activities recorded in GitLab repositories can be utilized to measure team productivity and monitor project progress continuously. However, monitoring activities directly through GitLab repositories is often less effective because information is not presented in a centralized and real-time manner.This study aims to analyze the implementation of a web-based developer productivity monitoring dashboard using GitLab API and n8n integration with the Prototype method. The Prototype method consists of communication, quick design, build prototype, user evaluation, and refinement prototype stages to ensure the system meets user requirements. GitLab API serves as the primary data source using Personal Access Token authentication, while n8n is utilized as a workflow automation platform to process repository and commit activity data automatically. The dashboard is developed using HTML, CSS, and JavaScript and is integrated with webhooks to enable real- time data synchronization. The results indicate that the system successfully integrates GitLab API with the monitoring dashboard, enabling the display of repository information, commit activities, developer productivity metrics, data visualization charts, and developer rankings based on commit contributions. The system also provides automatic notifications through Telegram, WhatsApp, and email whenever new repository activities occur. Testing results demonstrate that all system features function according to user requirements and improve the effectiveness of monitoring software development activities in a faster, more structured, and real-time manner.